PERBANDINGAN TINGKAT PENGEMBALIAN DAN RISIKO SEBELUM DAN KONDISI MULAI COVID-19 SERTA PADA POSISI REBOUND SAHAM - Sunaryo naryo Sunaryo (Mediastima, 2021)
The purpose of this research was to determine the difference in the rate of return on shares and the rate of risk in the stock sectors before, during the Covid-19 conditions and the rebound position. The sample used in this research is all sectors on the Indonesia Stock Exchange, and the period is September to December 2019, from January to April 2020, and from September to December 2020. The analysis method used in this research is descriptive which includes average return, standard deviation, volatility and coefficient of variance. The results of the study found that the rate of return of stock sectors on the IDX in the conditions of the outbreak of Covid-19 decreased compared to before the outbreak of Covid-19, and there was an increase in the rate of return in a rebound position. The risk level of the stock sectors on the IDX in the conditions of the outbreak of Covid-19 increased compared to before the outbreak of Covid-19, and there was a decrease in the level of risk in a rebound position.